2019
DOI: 10.3390/nu11030563
|View full text |Cite
|
Sign up to set email alerts
|

Total, Fresh, Lean, and Fresh Lean Beef Consumption in Relation to Nutrient Intakes and Diet Quality among U.S. Adults, 2005–2016

Abstract: (1) Background: This study assessed the influence of beef consumption on nutrient intakes and diet quality among U.S. adults. (2) Methods: Nationally-representative sample (n = 27,117) from 2005–2016 National Health and Nutrition Examination Survey was analyzed. First-difference estimator addressed confounding bias from time-invariant unobservables (e.g., eating habits, taste preferences) by using within-individual variations in beef consumption between 2 nonconsecutive 24 h dietary recalls. (3) Results: Appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…A difference between white and AA populations could be due to differences in types of processed and unprocessed red meat consumed or differences in cooking methods. For example, AAs are less likely to consume lean beef compared with whites (23) and more likely to use frying as the cooking method (24). In the BWHS, we did not have sufficient information to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…A difference between white and AA populations could be due to differences in types of processed and unprocessed red meat consumed or differences in cooking methods. For example, AAs are less likely to consume lean beef compared with whites (23) and more likely to use frying as the cooking method (24). In the BWHS, we did not have sufficient information to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to complete two 24-h dietary recalls for each cycle except only once in the 1999–2000 wave. Each food consumption was assigned an 8-digit Food and Nutrient Database for Dietary Studies (FNDDS) code and the code for beef products was 21000000–21800000 ( 29 ). We assessed the beef intake by calculating the sum of the weight of all beef products consumed by participants over a 24-h dietary recall.…”
Section: Methodsmentioning
confidence: 99%
“…Globally, national dietary surveys report that fresh red meat including beef and lamb (and their dishes) make important contributions to intakes of protein, vitamin B12, vitamin D, iron, zinc and selenium [ 19 , 20 , 21 , 22 , 23 , 24 ]. A recent study in the UK has shown that females (a population group who already have some of the lowest red meat intakes) with intakes of red meat < 40 g/day were more likely to have intakes of iron, zinc, vitamin B12 and potassium below the lower reference nutrient intake (LRNI) than those with intakes of >40 g/d [ 25 ].…”
Section: Introductionmentioning
confidence: 99%